Formation, Regulation, and Repair: A Dynamic Consumer Trust Mechanism in Live-Streaming E-Commerce - He, Jiarong (Transactions on Social Science, Education and Humanities Research, 2026)
With the growth of platform and live streaming technologies, e-commerce live streaming has become a key form of consumption and communication in the digital economy. By improving information visibility and interactivity, it reduces consumers’ search costs, enhances decision-making efficiency, and fosters trust through bidirectional interaction. However, trust in this context is not spontaneous—it is co-constructed by multiple agents and shaped by ongoing processes rather than existing as a static outcome. This study explores how consumer trust is dynamically constructed in e-commerce live streaming from the perspectives of streamers, products, and platforms. Using a grounded theory approach, we conducted in-depth interviews with 22 users who had experience with live streaming shopping and had established trust in this transaction mode. Based on interview data, we developed a theoretical model of consumer trust mechanisms and analyzed how the three dimensions jointly influence trust orientation and subsequent purchasing behavior. Findings indicate that consumer trust is synergistically shaped by multiple factors and evolves through micro-processes of trust building, modulation, and repair. This research contributes to the understanding of dynamic trust in live streaming contexts and offers practical insights for improving user experience and supporting the sustainable development of the e-commerce ecosystem.